Die vorletzte Freiheit - Auch, Stefan (Germany Czech Republic, 2018)
The blue sky arching above the young boy in Auschwitz-Birkenau is his refuge. And so it remains. Otto Dov Kulka, survivor of the Family Camp and prominent historian, long retained deep within himself the memories of his childhood in the Metropolis of Death.
Verzio Film Festival Submission
Keywords: Documentary films